Coronary Microvascular Angina: A State-of-the-Art Review - Spione, Francesco; Arevalos, Victor; Gabani, Rami; Sabaté, Manel; Brugaletta, Salvatore (Frontiers in Cardiovascular Medicine, 2022)
Up to 60–70% of patients, undergoing invasive coronary angiography due to angina and demonstrable myocardial ischemia with provocative tests, do not have any obstructive coronary disease. Coronary microvascular angina due to a dysfunction of the coronary microcirculation is the underlying cause in almost 50% of these patients, associated with a bad prognosis and poor quality of life. In recent years, progress has been made in the diagnosis and management of this condition. The aim of this review is to provide an insight into current knowledge of this condition, from current diagnostic methods to the latest treatments.